DAMPAK POLA ASUH ORANG TUA TERHADAP REPRESI EMOSI PADA REMAJA – DEWASA MUDA - Eoh, Tiffany Aimee P; Gani, Anezka Raphael; Dewi, Jennifer Felda; Prayogi, Sydney Siloam; Hariyanto (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
The purpose of this study was to identify the types of parenting styles that are associated with adolescence and young adult emotional regulation skills, and to explore their long-term impact on their emotional health. Using a survey method with an online questionnaire, this study involved 30 participants aged between 12 – 25 years. Parenting styles were categorized into four types: authoritarian, authoritative, permissive, and neglectful. The results showed that authoritarian parenting was associated with high levels of emotional repression, which is often associated with anxiety disorders, frustration, and depression. Authoritative parenting showed more controlled emotional repression, while permissive parenting had a passive impact on emotional regulation. No participants reported neglectful parenting, most likely due to limitations in sampling. These findings emphasize the importance of supportive parenting in the formation of healthy emotional regulation skills in adolescents and young adults, as well as the urgency to create a more balanced and responsive parenting environment to their emotional needs. This study is expected to provide insight for parents and practitioners in developing more effective parenting strategies